Development of platinum(II) and -(IV) CNC pincer complexes and their application in a hydrovinylation reaction - Serra, Daniel; Cao, Peng; Cabrera, José; Padilla, Robin; Rominger, Frank; Limbach, Michael (Organometallics, 2011)
A series of new, dicationic platinum(II) CNC pincer complexes were prepared and characterized by NMR and X-ray diffraction analysis. Oxidative addition of methyl iodide and iodine yielded the mostly unstable platinum(IV) complexes, which readily underwent reductive elimination to yield the platinum(II) precursors. Nonetheless, a platinum(IV) iodide adduct was isolated and was characterized by X-ray diffraction analysis. Additionally, a platinum(II) ethylene complex was isolated and found to be a moderately active yet highly selective catalyst in the co-dimerization of 2-methyl-2-butene with ethylene.